Rifampin vs. rifapentine: what is the preferred rifamycin for tuberculosis?. Issue 10 (3rd October 2017) - Alfarisi, Omamah; Alghamdi, Wael A.; Al-Shaer, Mohammad H.; Dooley, Kelly E.; Peloquin, Charles A.
ABSTRACT: Introduction : One-third of the world's population is infected with Mycobacterium tuberculosis (M.tb.) . Latent tuberculosis infection (LTBI) can progress to tuberculosis disease, the leading cause of death by infection. Rifamycin antibiotics, like rifampin and rifapentine, have unique sterilizing activity against M.tb . What are the advantages of each for LTBI or tuberculosis treatment? Areas covered : We review studies assessing the pharmacokinetics (PK), pharmacodynamics (PD), drug interaction risk, safety, and efficacy of rifampin and rifapentine and provide basis for comparing them. Expert commentary : Rifampin has shorter half-life, higher MIC against M.tb, lower protein binding, and better distribution into cavitary contents than rifapentine. Drug interactions for the two drugs maybe similar in magnitude. For LTBI, rifapentine is effective as convenient, once-weekly, 12-week course of treatment. Rifampin is also effective for LTBI, but must be given daily for four months, therefore, drug interactions are more problematic. For drug-sensitive tuberculosis disease, rifampin remains the standard of care. Safety profile of rifampin is better-described; adverse events differ somewhat for the two drugs. The registered once-weekly rifapentine regimen is inadequate, but higher doses of either drugs may shorten the treatment duration required for effective management of TB. Results of clinical trials evaluating high-dose rifamycin regimens are eagerly awaited.